Propagação vegetativa e análise da diversidade molecular em Handroanthus chrysotrichus (MART. ex DC) J. Mattos - Rabaiolli, Silvia Machado dos Santos (2019)
Considering the state of degradation of native forests, there is a growing concern about protecting the environment and sustainable production, so as not to interfere with the natural occurrence of forest resources and contribute to the recomposition of biodiversity. As a result, studies are needed to better understand the characteristics of native tree species, to obtain good quality seedlings, with conditions to resist adverse conditions, survive and grow at a level compatible with the economically expected. Handroanthus chrysotrichus (Mart. Ex DC.) J. Mattos, popularly known as ipê-amarelo, is a native species belonging to the Bignoniaceae family, which has economic, ecological and ornamental importance due to its characteristics. However, their seeds may lose viability during the storage period. The present work aimed to contribute with information related to vegetative propagation and molecular diversity in H. chrysotrichus. For adventitious rooting by minicutting, minicuttings of 8 cm were used, isolated from buds of ministrains of seminal origin. The root formation was evaluated after minicuttings were immersed in a solution containing 0, 1,000, 2,000 or 4,000 mg L-1 of IBA, after testing different types of substrates, apical and caulinares minicuttings and different seasons of the year in two consecutive years. The productivity of the clonal minijardim was evaluated in two consecutive years. The acclimatization of the seedlings occurred in a greenhouse for 30 days, and later the plants were taken to the field, and an initial evaluation was performed after 30 days. The rhizogenesis in minicuttings was satisfactory with the use of up to 2,000 mg L-1 of IBA, with a period of 60 days sufficient for the formation of roots. Better results were obtained in the presence of vermiculite substrate and with apical minicuttings. Spring and summer were the seasons with the highest percentage of rooting. In the first year of evaluation, the higher productivity of ministrains occurred in the summer while for year 2 was in the spring. After 30 days of acclimatization, 100% of minicuttings survived and after 30 days in field conditions, a 65% survival of the plants was observed. In the analysis of the genetic diversity of the H. chrysotrichus experimental stand, the transferability of four microsatellite loci developed for Tabebuia roseo-alba, in 13 individuals selected as seed door trees was analysed. The results of the present study revealed the existence of genetic variability in the studied population, demonstrating success in the transferability of the selected markers.